Determination of specific attenuation for satellite links in equatorial-tropical region - Yasser Asrul Ahmad (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Satellite technology is coping with the advancement in bandwidth and technology in terrestrial communication by incorporating new technology for Fixed Satellite Services (FSS) and Broadcast Satellite Services (BSS) for communication satellite located in the geostationary orbit recognised as High Throughput Satellite (HTS). Compare to conventional communication satellite, HTS provides larger bandwidth and operates at higher frequency bands mainly in the Ku and Ka-band. However, Ku-band and frequencies above 10 GHz are well known to be susceptible to rain hence require larger rain fade margin. On top of that, the equatorial region has a heavier rainfall rate than the temperate climate hence worsening the rain attenuation. The widely used rain attenuation model such as the ITU-R and other rain models have not been successful to accurately predict the rain attenuation in equatorial region particularly with tropical condition. The specific attenuation is the major component in determining the rain attenuation prediction. This research aims to evaluate and analyse specific attenuation in the equatorial region for satellite link exposed to heavy rainfall. This research also aims to produce a simplified specific attenuation model to be used in the prediction of satellite communication links in the tropical-equatorial region to improve the rain attenuation prediction. Three frequencies, each from C, Ku and Ka-band are measured using commercial earth station systems belongs to MEASAT and ASTRO. At the same time, the point rainfall rate is measured. The rain attenuations from each frequency bands are then correlated with the rainfall rate to produce specific attenuation. The regression analysis is used to produce the measured specific attenuation coefficients at each frequency and further analysed into models for k and α coefficients. At the same time, the areal rainfall rate is measured from five rain gauges using the Department of Irrigation and Drainage rainfall stations. The rainfall rate distribution from the five stations is modelled into a local rainfall rate model. Together, the rainfall rate model and specific attenuation coefficients produce a specific attenuation model based on the power law form. The proposed specific attenuation produces, specific attenuation for frequencies ranging from 4 GHz to 21 GHz suitable for satellite communication links in the equatorial region. Out of the ten rain attenuation models evaluated, two rain attenuation models which are Crane Global and SAM showed the best agreement for the equatorial region. The modified specific attenuation model implemented with Crane Global and SAM model made a 68% and 59% improvement for Ku-band and 21% and 24% improvement for Ka-band in term of root mean square error (RMSE), respectively. Implementing the modified specific attenuation model into various rain attenuation models has shown improvement to the prediction of rain attenuation in the tropical-equatorial region.